Proposta de elaboração de um glossário bilíngue de termos simples, expressões fixas e semifixas da área de sensoriamento remoto - Hasmann, Dalila dos Santos [UNESP] (2013)
Brazil was one of the countries that stood out in the list of nations that publishes more articles in scientific journals. From 2007 to 2008, the Brazilian scientific production has moved from 15th to 13rd place in the world ranking published articles in professional journals. However, 60% of articles published by the Brazilians are in Portuguese, which makes the Brazilian work have little international attention. The purpose of this research is to build and analyze a parallel corpus composed of a book of Remote Sensing and its translation in the direction English into Portuguese in order to create a glossary of most recurrent terms in the literature of Remote Sensing. The achievement of these goals will take for theoretical and methodological foundation the Corpus-Based Translation Studies (BAKER, 1993, 1995, 1996; CAMARGO, 2005), Corpus Linguistics (BERBER SARDINHA, 2004) and principles of Terminology (BARROS, 2004; KRIEGER & FINATTO, 2004). It will also use Wordsmith Tools program and its tools. Besides the parallel corpus, we will also build two comparable corpora respectively from articles published in Brazilian and international journals in the area. The first results show that the translators made use of greater variation of vocabulary in their translations, which can be a way to make the text more clear to the reader. For the analysis of glossary entries, professionals from the National Institute for Space Research - INPE, will be consulted and their views aggregated to this research to give consistency to the production of the proposed bilingual glossary.